2010
DOI: 10.1007/s00442-009-1561-0
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen uptake and nitrogen use efficiency above and below ground along a topographic gradient of soil nitrogen availability

Abstract: Nitrogen (N) uptake and nitrogen use efficiency (NUE) are closely related through feedback mechanisms to soil N availability and N cycling in forested ecosystems. We investigated N uptake and NUE not only at the leaf, litterfall, and aboveground levels but also belowground and whole stand levels along a topographic gradient of soil N availability in a cool temperate deciduous forest in Japan. In this study, we addressed how whole stand level N uptake and NUE affect C and N cycling in forested ecosystems. At th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…The annual NPP, including the aboveground NPP (ANPP) and belowground NPP (BNPP) of vegetation were calculated using the following equations47:…”
Section: Methodsmentioning
confidence: 99%
“…The annual NPP, including the aboveground NPP (ANPP) and belowground NPP (BNPP) of vegetation were calculated using the following equations47:…”
Section: Methodsmentioning
confidence: 99%
“…2). Several studies have shown a similar pattern along a topographic gradient (Nakanishi et al 2009;Tateno and Takeda 2010). These findings suggest that leaf N concentration can be determined by soil chemical properties such as soil pH and C/N ratio in the site but vary with micro-topographic relief within the area.…”
Section: Leaf Propertiesmentioning
confidence: 52%
“…In addition to increasing atmospheric CO 2 , the natural level of biologically available N inputs to terrestrial ecosystems has roughly doubled, due to agricultural intensification and expansion and fossil fuel combustion (Matson et al 2002). Numerous studies have reported that increasing N availability can decrease N use efficiency by increasing plant N concentration or reducing photosynthetic carbon assimilation rate (Pastor and Bridgham 1999;Hidaka and Kitayama 2009;Tateno and Takeda 2010). However, most of the studies focused on the leaf-level nutrient use rather than the whole plant level.…”
Section: Introductionmentioning
confidence: 98%